Strategi Takmir Masjid At-Taqwa dalam Mengelola Keuangan untuk Progam Sosial dan Dakwah: At-Taqwa Mosque Takmir's Strategy in Managing Finances for Social and Da'wah Programs - Rahma Dzakiyyah; Novie Andriani Zakariya (Litera Academica Publishing, 2025)
This study aims to analyze the strategy of the At-Taqwa Mosque management in managing finances to support social and da'wah programs. This study is motivated by the need for transparent, accountable, and professional mosque financial management, considering that most mosques in Indonesia still use traditional systems despite having significant potential for congregational funds. The study used qualitative descriptive methods through interviews and documentation to explore four main aspects of financial management: budget planning, transaction recording, periodic reporting, and internal evaluation. The results show that the At-Taqwa Mosque has implemented good governance principles through open monthly reporting, manual and digital recording, and deliberation-based decision-making. Financial stability is strengthened through diversification of funding sources such as congregational donations, regular donors, QRIS, and rental of mosque facilities. These funds are allocated for social programs—including educational assistance, interest-free loans, and charity—as well as da'wah programs such as TPA (Teaching and Religious Education Center), religious study groups, and community religious activities. These findings indicate that structured financial management supported by digitalization can increase congregational trust, program effectiveness, and the sustainability of mosque activities. This study provides implications that the modern financial governance model can be replicated in other mosques, although the research is still limited to one location and a small number of informants, so further research with a wider scope is needed.